PERSEPSI PENGUNJUNG TERHADAP OBJEK WISATA PANTAI MARINES ECO PARK DI PESAWARAN PROVINSI LAMPUNG - Kusuma, Alan Budi; Winarno, Gunardi Djoko; Rusita; Iswandaru, Dian (Jurusan Kehutanan, 2022)
Visitors' perception of tourist objects is essential in tourism development because it is one of the indicators that can be used as a reference in tourism management. Good tourism management can be done by developing supporting facilities that can create opportunities to increase tourist interest. This study aims to analyze the supporting facilities of Marines Eco Park Beach Tourism objects in Pesawaran Regency and to determine visitor perceptions of the development of tourist objects with 4A aspects (attraction, accessibility, amenities, and ancillary service). The research was conducted in April-May 2022. Data collection was carried out using observation and interview methods. Respondents from the management were determined using a purposive sampling technique, visitor respondents were determined using a random sampling technique with an age limit of â‰¥17 years, and then the data were analyzed through the descriptive qualitative method. The results showed that the facilities offered by the Marines Eco Park Beach Tourism manager consist of toilets, gazebos, places of worship or prayer rooms, canteens and stalls, security posts or monitoring posts, parking lots, and trash bins. While the most supportive facilities, namely cafes and restaurants. Perception assessment of the 4A aspect (attraction, accessibility, amenities, and ancillary service) shows that the perception of visitors at Marines Eco Park Beach Tourism is in the neutral category. Therefore, the Marines Eco Park Beach Tourism Manager is expected to be able to carry out tourism development optimally, especially by adding the facilities needed by visitors.